Seismic Anisotropy and Intraslab Hydrated Faults Beneath the NE Japan Forearc - Wang, Zewei; Zhao, Dapeng; Chen, Xiaofei (Geophysical research letters, 2022)
The water cycle in subduction zones is closely related to the generation of large earthquakes and arc magmas. Outer‐rise hydrated faults subducting with the oceanic lithosphere are suspected to be important for the water cycle. However, geophysical evidence for the intraslab hydrated faults beneath forearc is scarce. Here we present high‐resolution P‐wave anisotropic tomography of the Tohoku forearc derived from arrival‐time data recorded at both onshore and offshore seismic stations. Trench‐parallel intraslab fast velocity planes of anisotropy are revealed that intersect the slab upper surface at high angles (∼45°–90°), reflecting aligned hydrated faults in the slab. Ruptures of the hydrated faults may cause large intraslab earthquakes. The hydrated‐fault associated water entering a large near‐trench asperity in the megathrust zone could have triggered the great 2011 Tohoku‐oki earthquake (Mw 9.0). Plain Language Summary The water entering subduction zones is thought to be a crucial incentive for large earthquakes and arc magmas. Plate‐bending associated normal faults in the outer‐rise region prior to subduction are invaded by seawater and serpentinized to form hydrated faults. The subduction of the hydrated faults with the oceanic lithosphere is suggested to be an important transport route for seawater into the deep mantle. However, geophysical evidence for the existence of these hydrated faults beneath forearc is still lacking. Here we present an anisotropic tomography model showing that anisotropy in the forearc segment of the slab is well consistent with the feature caused by the subducted hydrated faults. Large intraslab earthquakes (M 7.1) in 2011 and 2021 beneath the Tohoku forearc were probably caused by ruptures of the hydrated faults. Furthermore, the hydrated‐fault associated water entering a large asperity in the megathrust zone near the Japan Trench could have triggered the great 2011 Tohoku‐oki earthquake (Mw 9.0). Key Points Trench‐parallel intraslab fast velocity planes of anisotropy reflect aligned hydrated faults in the slab Ruptures of the hydrated faults in the slab may cause large intraslab earthquakes The hydrated‐fault‐associated water entering a large asperity triggered the great 2011 Tohoku‐oki earthquake